Eksplorasi dan Pemberdayaan Masyarakat untuk Pencegahan Stunting di Desa Bulurejo dengan Pendekatan Komunitas Secara Komprehensif - Aqsa Aufa Syauqi Sadana; Yudhy Dharmawan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The incidence of stunting in Indonesia remains a major public health concern. Child, parent, household, neighborhood, and community characteristics and factors were strongly associated with the incidence of stunting. Stunting not only affects children's physical growth but also has a direct impact on cognitive development and future learning ability. Bulurejo Village, Wonogiri, is a rural area facing serious challenges related to nutrition and stunting of children. In general, the goal of this program is to raise awareness of the importance of early screening and stunting prevention in Bulurejo Village and to improve the community's knowledge of balanced nutrition and child health practices. Therefore, they can implement community-based stunting prevention measures. The program included exploration as a stunting screening effort and continued with community empowerment through community education and counseling activities. Overall, the total number of toddlers measured in the screening process was 104 out of 107 toddlers (98%) in seven hamlets, which shows an STD% stunting incidence rate of 13.4% in the July 2024 measurement period. The results of community counseling evaluated using the pretest and posttest showed an increase in knowledge from 30% of participants who knew stunting to 75% after counseling. Health promotion is the initial and main stage of the stunting prevention process in Bulurejo Village. Community-based empowerment has been proven to be an effective method for increasing community knowledge, especially regarding stunting. This program successfully explored the problem of stunting and empowering communities through education and training. The program is expected to continue and expand by involving more community members and the capacity of health cadres.